Humic Substances from Daecheung Lake Sediment and Their Removal Efficiency by Alum Coagulation - Gyu Kim, Cheol (Asian Journal of Chemistry, 2012)
The humic substances from the sediment taken from Daecheung Lake of Korea were characterized and their removal efficiency by alum coagulation was investigated. And also the effects of coagulant doses and molecular weight distributions of humic substances on the coagulation performance were investigated. This study demonstrated that humic substances from Daecheung Lake sediment of Korea had the characteristics that were consistent with that of other humic substances sources; humic acid had high UV254-abs, specific UV-abs (SUVA) and THMFP values in comparison to that of fulvic acid. Alum coagulation can effectively remove more humic acid and higher apparent molecular weight fractions than fulvic acid and lower apparent molecular weight fractions of natural organic matter. The study results suggested that optimum alum coagulation could readily treat humic substances from Daecheung Lake sediment.